RANCANG BANGUN APLIKASI PENGENDALIAN BIAYA PRODUKSI PADA PT SINAR BAJA HUTAMA - Atmiko, Fendi Puji; Soebijono, Tony; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
PT. Sinar Baja Hutama located on Jl. Dupak Rukun No. 111 – Surabaya is a company engaged in the production heavy equipment such as : train equipment, road maintenance equipment, farming equipment, Stone / Coal Crusher Plant & Mobile, Batching Plant, Mining Processing, Conveyor System, and Dradger Pontoon. For product that have big size customer must order first, after customer deal with the product price, company will make the product. The problem that arises is when the work product for the manufacture turned out to cost less, and the company could not for additional cost to the customer so the company had to bear the cost of production. Based on the existing problem, data processing needs to be done in order to produce a value in the form of information used as budgetary control cost in the production process. Application control production costs will be made to have a function as a control costs against budget plan that was made before, on that application administrators can control costs by considering certain aspects, including the price of the main raw and auxiliary materials, machinery costs, installation costs and employee wages. With so can minimize the cost of production shortages. The information generated from the application is the Realization report production cost, budget compared to actual reports, and production progress report of the work for each product. In addition there is a notification as if the cost of cost control has reached the point that they think will lead to swelling production costs. With the above applications can minimize shortages company production costs, as well as from reports generated will be a benchmark for the manufacture of the next product.